Charcot-Marie-Tooth disease type 4H caused by FGD4 gene variation: two families report and literature review - ZHAN Fei-xia; JIANG Qing-qing; LÜ Wen-lu; TIAN Wo-tu; LUAN Xing-hua; CAO Li (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To report 2 cases of Charcot-Marie-Tooth disease type 4H (CMT4H) caused by FGD4 gene variation and review the relevant literatures, summarizing the clinical and gene mutation characteristics of CMT4H. Methods and Results Two families with CMT4H diagnosed by genetic test in Shanghai Sixth People's Hospital Affiliated to Shanghai Jiaotong University School of Medicine from May 2020 to July 2022 were included. The probands in 2 families were both sporadic patients with onset in early adolescence, manifesting as progressive postural gait abnormalities, difficulty walking, and foot deformities. Nerve electrophysiological examination showed multiple demyelinating damages to sensory and motor nerves. Sural nerve biopsy in proband of family 1 disclosed a decreased density of myelin fibers and demyelinating neuropathy with thickened and excessively folded myelin sheath. Whole exome sequencing (WES) revealed that both probands had compound heterozygous mutations in the FGD4 gene, all of which were novel, and cosegregated with the family members. Conclusions CMT4H is a peripheral neuropathy mainly caused by autosomal recessive demyelination, and case report from 2 families further expand the spectrum of FGD4 gene mutations.